P18 Post exposure prophylaxis following possible exposure to HIV infection: an evaluation of 391 attendances at three central London sexual health clinics. (23rd May 2012) - Janmohamed, K; Bull, L; Payne, D; Cooper, F; Lake, C; Nwokolo, N; Natha, M
Abstract : Background: Providing post exposure prophylaxis (PEP) following possible HIV exposure is a common GU presentation. However, few studies have evaluated this practice. Aim(s)/Objective(s): To answer the following on PEP presentations: age, sex, nature of exposure to HIV, time to presentation for PEP, side effects, completion rates, presence of sexually transmitted infections (STIs), appropriateness of PEP dispensing and comparisons of findings with other published studies. Methods: GUM clinic attendances were evaluated from April 2009 to March 2010. Results: There were 391 PEP attendances: 373 males (96% MSM), 18 females. Age range 19–57 (mean 35.4) years. Presentation followed anal sex in 89%, vaginal sex in 5%. The remainder attended following oral sex, splash incidents, injecting drug use, or other exposure. Forty six percent attended within 24 h, in one instance PEP was dispensed beyond 72 h. The majority completed PEP (82%). GI side effects were experienced by 60%. Baseline screening for hepatitis B showed active infection in 1% and immunity in 74%. A baseline HIV test was conducted in all but one patient. An STI screen was conducted at or around day 14 in 69% of patients, with 12% testing positive for an STI in line with previously published data. Follow-up rate at 3–6 months was 52%: Of 203 patients tested for HIV at follow-up, 2 (1%) tested positive. Conclusions: PEP was dispensed appropriately in the majority of cases. The fact that 82% of individuals completed treatment despite side effects is likely to be due to the use of more tolerable regimens than were used historically. The presence of an STI in 12% of people tested highlights the importance of screening in individuals presenting for PEP. The fact that only 52% of patients attended for a follow-up HIV test at 3–6 months is of concern and warrants further exploration.